Ruang Lingkup dan Metode Pendidikan Akhlak (Telaah Hadits-hadits Kitab Akhlaq Lil Banin Juz IV) - Cecilia, Vera; Saputra, Rido (Journal of Innovation in Teaching and Instructional Media, 2023)
In the educational process, methods have a very significant position in achieving goals, even methods as an art in transferring knowledge or subject matter to students are considered more significant than the material itself. The method is much more important than the material in the selection and use of a method that must be conveyed. The data collection method used by researchers in this research is a qualitative method which includes (secondary data and primary data) while for secondary data in the form of the scope and methods of moral education, data obtained from the book of akhlaq lil banin, previous research journals related to hadith-hadith of morality lil banin. The research results show that the moral education method reviewed from the book Akhlaq Lil Banin confirms that there are two methods that can be used, namely the story method and the example method.